2023
DOI: 10.3390/molecules28062642
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Photosynthesis Efficiency in Melissa officinalis Subjected to Heavy Metals Stress

Abstract: The aim of this study was to assess influence of cadmium and zinc treatments on antioxidant activity combined with the photosynthesis efficiency in a popular herb lemon balm (Melissa officinalis L.). Plants were grown under greenhouse conditions by the pot method. The Mn, Cu, Cd, and Zn contents in soil and plants were measured by HR-CS FAAS. The activity of net photosynthesis, stomatal conductance, transpiration rate, intercellular CO2, and index of chlorophyll in leaves were determined for all investigated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This showed that Cd stress has serious toxic effects on photosynthesis, such as light absorption and electron transfer. This result was consistent with findings that photosynthesis is a sensitive biological process that occurs in response to Cd stress [ 48 , 49 ]. Overall, Cd stress is inducible and involves transient photosynthetic heterogeneity as an emergency defense mechanism for M .…”
Section: Discussionsupporting
confidence: 93%
“…This showed that Cd stress has serious toxic effects on photosynthesis, such as light absorption and electron transfer. This result was consistent with findings that photosynthesis is a sensitive biological process that occurs in response to Cd stress [ 48 , 49 ]. Overall, Cd stress is inducible and involves transient photosynthetic heterogeneity as an emergency defense mechanism for M .…”
Section: Discussionsupporting
confidence: 93%
“…It has antibacterial and calming properties [30,31]. The quality of herbs, their extracts and essential oils strongly depends on the plants' development and their growing conditions [32]. Herb crops require appropriate fertilization, and the number of permissible plant protection products is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are many research studies reported on the strong correlation between the antioxidant effect of medicinal plants and their flavonoid content [12,19,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], especially this Asian water lily plant [8,9,12,18,19,22]. Our previous work investigated flavonoid profiles from both stamen and perianth ethanolic extracts of this medicinal plant at the population level to study the antioxidant potential of Asian water lily populations throughout Thailand using difference assays to detecting different antioxidant mechanisms [9].…”
Section: Introductionmentioning
confidence: 99%